"الخدمة المجتمعية كعقوبة بديلة للعقوبات المقيدة للحرية في الأمارات "النظرية والتطبيق - Nasser Sultan Nasser Al Ghaith
This Search addresses the community service as an alternative punishment for imprisonment between theory and practice in the light of the UAE legislation and the ministerial and administrative decisions regulating it. It is important because it addresses a modem penal model with clear privacy and importance. As a substitute punishment, the UAE has activated this punishment because it gives the convict a sense of responsibility towards his society. It benefits the public and society as a whole, contributes to the process of reform and rehabilitation, and reduces the rate of return to crime, because it keeps the convict in touch with his community and family. In order to achieve the objectives of the research, the researcher relied on the analytical descriptive approach to identify all aspects related to the punishment of community service, in order to reach indicators of value that support the subject of the research. The comparative method was also used by the legal texts in UAE legislation and comparative Arab and foreign laws. The research issue is how to evaluate the effectiveness of community service in reflecting the policy of social reintegration of detainees compared to the restrictions on freedom, the effectiveness of the monitoring system of the convict during the implementation of the penalty for community service, and the non- consent of the sentenced to accept community service in UAE legislation which may face a state of criticism for human rights considerations on the one hand, and on the other impede the achievement of the desired objectives. In addition, the UAE legislation does not speci@ the nature of the legal relation between the convict and the party in whose favor the service is carried. Additionally, there is a distinctive lack of identification of the work of community service and its fields, and left to be determined by a decision issued by the Council of Ministers, in one of the institutions or establishments to be determined by a decision of the Minister Justice, in agreement with the Ministers of the Interior, Human Resources and Resettlement, or by a decision of the competent judicial authority, without requiring the controls to be taken into account in the selection of the business. The failure to provide for the rules that are subject to the implementation process raises many legal problems that must be addressed. The study concludes that the UAE legislator adopted the punishment of community service in line with the clear development of punitive policy and the concept of punishment, to integrate convicted persons in the society system and create psychological and physical balance, and to provide new alternative solutions to freedom-restricting penalties that proved ineffectiveness. The system of community service as an alternative punishment for fieedom-related penalties is linked to the existence of a clear system of implementation and follow-up. It provides the awareness of those who will be subject to the punishment, and more importantly the extent of community awareness and acceptance of such sanctions. In addition, the UAE legislation did not impose the consent of the sentenced person when imposing this penalty, other than some of the comparative legislation that stipulated his consent. The study also found a number of recommendations, the most important of which is the need for the competent judicial authority to consider, in issuing its judgment on community service, the proportion of the sentenced person's work in terms of its type and duration with the seriousness of the crime committed and its physical capacity. In order to ensure the effectiveness of the application of the penalty of community service, the principle of the non-coercion of a person to act and be voluntary based on free choice must be respected and compatible with the principle of consonance provided for in Article 34 of the Constitution of the United Arab Emirates, oversees its implementation and follow-up to achieve its objectives.